Corporate social responsibility (CSR) and labour rights in the People's Republic of China - Tatjana Chahoud (Deutsches Institut für Entwicklungspolitik (DIE), 2008)
With the rapid economic growth of the People's Republic of China, the living standards of most Chinese have improved, and the number living below the poverty line has been halved. Despite this, development in China faces major social and ecological challenges, which are reflected in growing environmental problems and an increase in social unrest. This and the growing pressure on Chinese businesses forming part of global value added chains to comply with international standards have put CSR and the strengthening of labour rights on the political agenda. These rights are important elements of the “harmonious society” that China is seeking to build. Crucial in this context are the initiatives taken to introduce the CSC 9000T standard in the textile and apparel industry and the recent government instructions to introduce CSR in Chinese state-owned enterprises. The strengthening of labour rights hinges on the Labour Contract Law (LCL), which entered into force in 2008. It requires labour contracts to be drawn up in writing and greatly restricts short-term employment relationships. The real contribution this agenda will make largely depends on whether and to what extent China succeeds in putting the CSR initiatives into practice, extending them to provincial level, increasing the number of businesses involved and establishing convincing verification mechanisms. The importance of the LCL will very much depend on whether the implementing provisions are so worded that any circumvention (through part-time contracts, for example) is prevented. In addition, Chinese labour law must not only strengthen individual workers' rights but introduce, in accordance with the conventions of the International Labour Organization (ILO), rules on the settlement of collective disputes. International organisations, multinational corporations, including German companies, and the German development cooperation community can help to strengthen China's capacities in this area with individual projects and good practices.
Keywords: 330